Exercise Does Not Prevent Thermoregulatory Adaptation to Cold Stress During the Winter Season - Dae-Hwan Kim; Min-Hyeok Jang; Jean-Hee Han; Jung-Hyun Kim (운동과학)
PURPOSE Despite the growing need for recreation and work in cold environments, which often involve high levels of physical activity and significant body heat loss, studies investigating the impact of exercise during repeated cold exposure on cold adaptation are lacking. Therefore, this study aimed to examine whether exercise during repeated cold exposure during winter influences thermoregulatory adaptation to cold. METHODS Forty young male participants were recruited and classified into two groups: cold weather athletes (CA) who spent at least 10 hr per week training outdoors, and non-athletes (CON) who did not regularly exercise outdoors but were naturally exposed to cold during the winter season. Physiological and perceptual thermoregulatory responses were assessed before and after winter. RESULTS After winter (December-February), both groups exhibited cold habituation features (p<.05; higher body temperature, blunted sympathetic response, and attenuated cold sensitivity), except for cold pain in the CA group. The cold-induced vasodilation (CIVD) response was enhanced in both groups (F=6.864, p=.034), as indicated by the higher temperature parameters of the fingers (Tmax, Tmean, and Tmin). However, the enhanced temperature response did not translate into improved manual dexterity following cold-water immersion (F=0.041, p=.841). CONCLUSIONS Exercise during repeated cold exposure did not prevent overall thermoregulatory adaptation after winter. However, the CA group exhibited an attenuated habituation to cold pain, suggesting a potential area for future research on the effects of exercise on cold adaptation. Although the CIVD response improved, it did not result in better fine manual dexterity after cold immersion. These findings highlight the need for further studies of the biological advantages of CIVD.